2022
DOI: 10.11603/ijmmr.2413-6077.2021.2.12657
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Immunoblot Results for Determination of Antibodies to Lyme Disease Pathogens in Children of Ternopil Region

Abstract: Background. Lyme disease (LD) is a multisystem disorder caused by Borrelia burgdorferi and other similar tick-borne Borrelia. Objective. The aim of the research was to compare the results of the serological examination of children with different forms of Lyme disease. Methods. We observed the group of children (n=178) aged 1 to 14 years who were bitten by ticks. The control group consisted of 30 healthy children. Ticks were identified using a stereomicroscopic SEO system which included a stereomicroscope, a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…The probable prevalence of LA is 31% overall and 45% in the presence of knee triage. Children with joint damage caused by Lyme disease are more likely to experience knee lesions, lower peripheral leukocytes and lower cell count of fiber in the joints; they are less likely to have a fever compared to children suffering from septic arthritis [9,10]. In our study, all patients had persistent pain joint syndrome.…”
Section: Case Presentationmentioning
confidence: 60%
“…The probable prevalence of LA is 31% overall and 45% in the presence of knee triage. Children with joint damage caused by Lyme disease are more likely to experience knee lesions, lower peripheral leukocytes and lower cell count of fiber in the joints; they are less likely to have a fever compared to children suffering from septic arthritis [9,10]. In our study, all patients had persistent pain joint syndrome.…”
Section: Case Presentationmentioning
confidence: 60%
“…These months are likely to be the time of the tick breeding cycle and the peak time for people to spend outdoors. According to scientific observations, the skin of the lower extremities, buttocks, abdomen and head in children are the most common areas of tick bites [6]. Most often, the bites were localised in the head (19 -30.6 %) and lower extremities (18 -29.03 %), trunk (9 -14.51 %), neck (8 -12.90 %), upper extremities (2 -3.22 %), abdomen (4 -6.44 %), and earlobe (2 -3.22 %) in the study group of children, which was confirmed by other studies [6,7].…”
Section: Methodsmentioning
confidence: 99%
“…Оцінка серединних рівнів СРП у пацієнтів встановила, що цей показник виявився найвищим у пацієнтів групи 3 і становив 5,0 [3,9; 12,0] мг/л, достовірно відрізняючись від такого як у пацієнтів групи 1 (р=0,02), де він склав 1,4 [0,6; 3,7] мг/л, так і групи 2 (р=0,02), у пацієнтів якої серединний рівень СРП становив 2,1 [1,5; 2,4] [13]. У дослідженні, проведеному у Тернополі, теж виявлено високі значення антитіл IgG до B. burgdorferi у пацієнтів з ранньою та пізньою дисемінованими стадіями ХЛ [14].…”
Section: педіатріяunclassified